2016
DOI: 10.1021/acs.est.5b06280
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Pollutants Sorbed to Ingested Microbeads from Personal Care Products Accumulate in Fish

Abstract: The prevalence of microplastics (<5 mm) in natural environments has become a widely recognized global problem. Microplastics have been shown to sorb chemical pollutants from their surrounding environment, thus raising concern as to their role in the movement of these pollutants through the food chain. This experiment investigated whether organic pollutants sorbed to microbeads (MBs) from personal care products were assimilated by fish following particle ingestion. Rainbow fish (Melanotaenia fluviatilis) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(176 citation statements)
references
References 42 publications
2
152
0
3
Order By: Relevance
“…There is now substantial action on this issue internationally, with several governments, including those of the USA and the UK, introducing legislative bans on microbeads in cosmetics and detergents, and many cosmetics companies voluntarily committing to halt their use of microplastics by 2020 [2,3]. New research on the effects of microbeads has revealed biological responses in both terrestrial and aquatic environments, with evidence demonstrating that microplastics reduce the survival and fitness of earthworms Lumbricus terrestris [4] and facilitate the accumulation of sorbed organic pollutants in fish [5]. Discussion of the use of gene editing to control invasive species or disease vectors, raised in our 2014 horizon scan [6], has increased dramatically over the past year, with a range of developments using clustered regularly interspaced short palindromic repeats (CRISPR).…”
Section: Aims Of Horizon Scanningmentioning
confidence: 99%
“…There is now substantial action on this issue internationally, with several governments, including those of the USA and the UK, introducing legislative bans on microbeads in cosmetics and detergents, and many cosmetics companies voluntarily committing to halt their use of microplastics by 2020 [2,3]. New research on the effects of microbeads has revealed biological responses in both terrestrial and aquatic environments, with evidence demonstrating that microplastics reduce the survival and fitness of earthworms Lumbricus terrestris [4] and facilitate the accumulation of sorbed organic pollutants in fish [5]. Discussion of the use of gene editing to control invasive species or disease vectors, raised in our 2014 horizon scan [6], has increased dramatically over the past year, with a range of developments using clustered regularly interspaced short palindromic repeats (CRISPR).…”
Section: Aims Of Horizon Scanningmentioning
confidence: 99%
“…9,10 To date, microplastic origins are incompletely understood, but they include primary and secondary sources, with the latter including breakdown of products upstream of, or within, the environment. 3 In situ environmental fragmentation 11 is a difficult-tocontrol microplastic source because it stems from larger plastic debris continuously entering the environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interactions of these fragments with planktonic organisms and their predators have also been reported (Lima et al, 2015Long et al, 2015;Panti et al, 2015;Cole et al, 2016). These organisms are prone to feed on available microplastics and promote the transfer of particles and sorbed pollutants throughout the trophic web (Dantas et al, 2012;Lusher et al, 2013;Rochman et al, 2013;Tanaka et al, 2013;Besseling et al, 2014;Sá et al, 2015;Ferreira et al, 2016;Lönnstedt and Eklöv, 2016;Wardrop et al, 2016).…”
Section: Distribution Of Plastics and The Effects Of Their Occurrencementioning
confidence: 93%
“…Great attention has been given to this size class of pollutant, as a fraction much more abundant and ubiquitous in the marine environment in terms of number of items, which occurs from mangrove creeks and estuaries to remote oceanic islands (Ivar do Sul et al, 2013;Lima et al, 2014Lima et al, , 2016. These fragments are likely to be the most hazardous to marine biota owing to their small size, physical harm, blockage, starvation and chemical contamination due to organic and inorganic pollutants absorbed by the ingested microplastic (Frias et al, 2010;Turner, 2010;Cole et al, 2011;Rochman et al, 2013;Tanaka et al, 2013;Lönnstedt and Eklöv, 2016;Wardrop et al, 2016).…”
Section: Introductionmentioning
confidence: 99%